P476 Characterization of cardiac conduction abnormalities reported in the phase 3 ELEVATE programme. (30th January 2023) - Vermeire, S; Yarur, A; Rubin, D T; Dubinsky, M C; Regueiro, M; Irving, P; Peyrin-Biroulet, L; Goetsch, M; Gu, G; Wu, J; Modesto, I; McDonnell, A; et al.
Abstract: Background: Etrasimod is an investigational, once-daily, oral, selective sphingosine 1-phosphate receptor 1, 4, 5 (S1P1, 4, 5 ) modulator in development for the treatment of moderately to severely active ulcerative colitis (UC). First-dose, transient heart rate (HR) reduction and cardiac conduction aberrations are a known, on-target effect of S1P receptor modulators. Here, we report characteristics of patients for whom adverse events (AEs) of bradycardia or atrioventricular (AV) block were reported in the phase 3 ELEVATE programme. Methods: In ELEVATE UC 52 (NCT03945188) and ELEVATE UC 12 (NCT03996369), patients (16-80 years) with moderately to severely active UC were randomised 2:1 to once-daily etrasimod 2 mg or placebo on study day 1 with no dose titration regimen. Cardiac conduction was evaluated in all patients with a 12-lead ECG during the screening period, prior to randomisation on day 1 (baseline), and 4-hours post-dose. Bradycardia was considered an AE of special interest if the HR was <40 bpm, or <50 bpm with associated symptoms, or the event led to study discontinuation. AV conduction delays were considered an AE of special interest if second degree AV block (Mobitz Type I/II) or higher, first degree AV block with PR interval >230 ms, or if associated with clinical symptoms. Results: A total of 9 events of bradycardia were reported in patients receiving etrasimod across both trials (Table 1). All but 1 event (8/9) were first reported on day 1 of treatment, with the remaining first reported on day 2 (none reported after day 2). Seven of 9 events were asymptomatic; the 2 symptomatic events (moderate dizziness; mild dizziness, palpitations) led to therapy discontinuation and resolved without additional intervention. No serious or severe events of bradycardia or hemodynamic changes were reported. Three AEs of AV block were reported in patients on etrasimod across both trials. All events occurred on day 1 during in-clinic ECG monitoring per study protocol and were nonserious, asymptomatic, and resolved without interventional treatment. Two events were first degree, one of which was pre-existing (treatment was discontinued); the other patient continued treatment and completed the study. The third event was second-degree (Mobitz Type I) (treatment was discontinued). Among the small sample size of 11 patients who experienced ≥1 AE of bradycardia or AV block, there were no baseline characteristics that could be used to predict these events (Table 2). Conclusion: Cardiac AEs with etrasimod were generally rare, mild, asymptomatic, and occurred on day 1 in association with the first dose. This is consistent with other S1P receptor modulators. Data from the ongoing 5-year open-label extension will further characterize the etrasimod safety profile.